The person and the polis faith and values within the secular state - Titus, Craig Steven 1959- (Arlington, Va Inst. for the Psychological Sciences Press, 2006)
A contemporary philosophy of action / Kenneth L. Schmitz -- In defense of moral realism / Daniel N. Robinson -- The concept of public morality / Robert P. George -- The maladies of the political class : when reasons cease to matter / Hadley Arkes -- From modern individual to the transmodern person / Paul C. Vitz -- The first institution of democracy : Tocqueville on religion : what faith adds to reason / Michael Novak -- Moral realism and Christian values / Romanus Cessario
A contemporary philosophy of action / Kenneth L. Schmitz -- In defense of moral realism / Daniel N. Robinson -- The concept of public morality / Robert P. George -- The maladies of the political class : when reasons cease to matter / Hadley Arkes -- From modern individual to the transmodern person / Paul C. Vitz -- The first institution of democracy : Tocqueville on religion : what faith adds to reason / Michael Novak -- Moral realism and Christian values / Romanus Cessario
Includes bibliographical references and indexes
Keywords: Catholic Church -- Doctrines; Christian Sociology -- Catholic Church -- Congresses; Christian Ethics -- Catholic authors; Christianity and politics -- Catholic Church -- Congresses; Aufsatzsammlung